In Memoriam – Professor Eugeniusz Jan DANICKI - KOZACZKA, Eugeniusz; KAWALEC, Adam; NOWICKI, Andrzej (Archives of Acoustics, 2016)
Professor Eugeniusz Danicki, a distinguished academic teacher, outstanding specialist in the theory and application of acoustic waves and electronics, passed away on 11 September, 2016.